The Potential of Cnidoscolus chayamansa Alchoholic Leaves Extract as Hypolipidemia Agent - Retno Sri Iswari; Ibnul Mubarok; Fitri Arum Sasi (Biosaintifika: Journal of Biology & Biology Education, 2020)
Cardiovascular disease caused by hyperlipidemia is the highest case in term of fatality of non-infectious disease in Indonesia. Cnidoscolus chayamansa is well known as a herb that has nutraceutical potential for medicine and likely as a hypolipidemia agent. Therefore, this study aimed to identify the optimal dose of C. chayamansa as a candidate to treat cardiovascular diseases. A total of 30 white rats were acclimatized in the laboratory for 14 days. After that, the rats were grouped into six groups, randomly, which including a healthy control group (K0), a negative control group or hyperlipidemic rats (K-), a positive control group or hyperlipidemia-induced rats that was supplemented with atorvastatin (K+), then a hyperlipidemic rats treated with alcoholic extract of C. chayamansa leaves at doses of 100 mg /kgBB /day for K1, 200 mg/ kgBB/ day for K2 and 400 mg/ KgBB/ day for K3. The results showed that K3 treatment is the most effective and optimum dose for lowering total cholesterol level at 76.81±1.10 mg/dl, triglycerides 72.39±1.66 mg/dl and LDL-C at 21.47±0.58 mg/dl. The aortic histology assessment also showed that the K- group had putative thrombus or plaque in intima, and it was not found in other groups. This research focused on the optimum dose and new usage of C. chayamansa, as an anti-inflammatory in atherosclerosis. By understanding the optimum dose of C. chayamansa, the community can apply and control the herb consumption for their own therapeutic properties. For future application, the herb is potentially developed as anti-atherogenic medicine.